Synthesis and Antibacterial Activity of Some Novel Chalcones and Pyrimidine-2-one Derivatives - Vashi, Kamal; Naik, H.B. (Asian Journal of Chemistry, 2016)
Some novel chalcone derivatives have been prepared by condensation of aryl aldehyde and 2-hydroxy 3-chlaro 5-ethyl acetophenone in alkaline ethanol while pyrimidine-2-one derivatives have been prepared by the condensation of chalcone and urea. Characterization and structural elucidation have been done on the basis of chemical, analytical and spectral analysis. The antibacterial activity of compounds has also been screened.